2013
DOI: 10.1021/mz400059w
|View full text |Cite
|
Sign up to set email alerts
|

Light-Healable Supramolecular Nanocomposites Based on Modified Cellulose Nanocrystals

Abstract: Polymers that can be repaired after being damaged are attractive, because this feature can improve the reliability, functionality, and lifetime of these materials. We report here light-healable nanocomposites based on a telechelic poly(ethylene-co-butylene) that was functionalized with hydrogen-bonding ureidopyrimidone (UPy) and cellulose nanocrystals (CNCs) decorated with the same binding motif. These nanocomposites show significantly improved mechanical properties when compared to the supramolecular polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(167 citation statements)
references
References 35 publications
6
160
1
Order By: Relevance
“…For the past few years, the preparation of cellulose nanocrystals (CNCs) and their application in composite materials have gained increasing attention because of their inherent properties like outstanding mechanical properties (elastic modulus of 130-150 GPa) (Iwamoto et al 2009), high specific surface area (up to several hundreds of m 2 /g) (Ng et al 2015), high length-to-width ratio (up to several hundreds) (Jonoobi et al 2015) combined with low density (1.6 g/cm 3 ) (Moon et al 2011), low thermal expansion (0.1 ppm K -1 ) (Song et al 2013), biodegradability and renewability. Due to their special intrinsic nanostructure and excellent properties, CNCs have wide application potential in nanomaterials, such as aerogels (Mueller et al 2015;yang et al 2015), biomedical materials (Domingues et al 2014;Dugan et al 2013;Jorfi and Foster 2015;Plackett et al 2014), packaging materials (Fortunati et al 2012;Li et al 2013b;Mihindukulasuriya and Lim 2014), optical (Biyani et al 2013;Schlesinger et al 2015) or electroconductive (Lyubimova et al 2015;Ning et al 2015;Shi et al 2013;Tang et al 2014) materials, and several mechanically reinforced nanocomposites (de Castro et al 2015;Habibi 2014;Jonoobi et al 2015;Ng et al 2015;Sapkota et al 2015;Therien-Aubin et al 2015;Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, the preparation of cellulose nanocrystals (CNCs) and their application in composite materials have gained increasing attention because of their inherent properties like outstanding mechanical properties (elastic modulus of 130-150 GPa) (Iwamoto et al 2009), high specific surface area (up to several hundreds of m 2 /g) (Ng et al 2015), high length-to-width ratio (up to several hundreds) (Jonoobi et al 2015) combined with low density (1.6 g/cm 3 ) (Moon et al 2011), low thermal expansion (0.1 ppm K -1 ) (Song et al 2013), biodegradability and renewability. Due to their special intrinsic nanostructure and excellent properties, CNCs have wide application potential in nanomaterials, such as aerogels (Mueller et al 2015;yang et al 2015), biomedical materials (Domingues et al 2014;Dugan et al 2013;Jorfi and Foster 2015;Plackett et al 2014), packaging materials (Fortunati et al 2012;Li et al 2013b;Mihindukulasuriya and Lim 2014), optical (Biyani et al 2013;Schlesinger et al 2015) or electroconductive (Lyubimova et al 2015;Ning et al 2015;Shi et al 2013;Tang et al 2014) materials, and several mechanically reinforced nanocomposites (de Castro et al 2015;Habibi 2014;Jonoobi et al 2015;Ng et al 2015;Sapkota et al 2015;Therien-Aubin et al 2015;Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…improve the homogeneity and healing behavior of the nanocomposite. The nanocomposites were fabricated from a telechelic PEB terminated with hydrogen-bonding UPy groups ( Figure 15) (vide supra) and CNCs that were similarly functionalized [113]. In this case, the nanocomposites were homogeneous and showed significantly improved mechanical properties up to a CNC content of 20 w/w%, i.e., a much higher CNC content could be incorporated than in the abovediscussed nanocomposites.…”
Section: Supramolecular Nanocompositesmentioning
confidence: 99%
“…In this case, the nanocomposites were homogeneous and showed significantly improved mechanical properties up to a CNC content of 20 w/w%, i.e., a much higher CNC content could be incorporated than in the abovediscussed nanocomposites. In the rubbery regime (20 °C), the tensile storage modulus increased the ureidopyrimidone (UPy) motif [113]. Building on the  bonded supramolecular polymers introduced by Fox et al [107],…”
Section: Supramolecular Nanocompositesmentioning
confidence: 99%
“…It was shown that under comparable conditions films of 15·[La(NTf 2 ) 3 ] healed more efficiently than films made from 15·[Zn(NTf 2 ) 2 ], consistent with the lower stability of La 3+ /Mebip complexes vis-à-vis the Zn 2+ /Mebipbased counterparts and a higher level of light-induced depolymerization of the former. The concept of photo-thermal induced healing of supramolecular materials is applicable to any supramolecular polymer with a binding motif that is sufficiently dynamic and the concept has now been utilized in a variety of materials systems [83][84][85]. The repeated healability of the metallo-supramolecular polymers discussed above implies that on the molecular level, mechanical damage exclusively causes (reversible) disassembly of the metal-ligand motifs, as shown schematically in Figure 22, and not cleavage of covalent bonds.…”
Section: Metal-ligand Interactionsmentioning
confidence: 99%